Personal autonomy as a key factor of human self-determination - Serdiuk, Liudmyla; Danyliuk, Ivan; Chaika, Galina (Social Welfare: Interdisciplinary Approach, 2018)
The article presents the research on psychological factors of personal autonomy as a self-determination need and as a component of psychological well-being. The analysis was carried out in two directions: within in the theory of self-determination and within the theory of psychological well-being. The greatest influence on autonomy development as a self-determination need have such predictors as goals in life, challenge, self-efficacy, self-acceptance, self-assurance, locus of control-life, locus of control-Self. Predictors that positively affect autonomy as a component of psychological well-being are: self-acceptance, acceptance of aggression, self-confidence, creativity, control, self-esteem. The article determines that autonomy as a self-determination need is based not only on self-acceptance with all advantages and disadvantages, but also on existence of a goal in life and personal internal powers to achieve this goal. Autonomy, as it is understood in the theory of psychological well-being, is a necessary, but insufficient condition for self-determination. For formation and development of self-determination it is necessary to have a life purpose that gives meaningfulness to human life.